Evaluation of the protective effects of morin against acrylamide‐induced lung toxicity by biomarkers of oxidative stress, inflammation, apoptosis, and autophagy. Issue 7 (14th February 2022) - Yesildag, Kerim; Eroz, Recep; Genc, Aydin; Dogan, Tuba; Satici, Emine
Abstract: Acrylamide (ACR) has genotoxic, neurotoxic, and carcinogenic effects. From past to present, various plants or their products have been used for therapeutic purposes such as morin. It was aimed to detect possible protective effects of morin vs ACR‐induced lung toxicity. The rats, treated with ACR alone or with morin for 10 consecutive days, were included in the study. A broad variety of biomarkers related to oxidative stress, apoptosis, autophagy, and inflammatory responses were evaluated. ACR increased malondialdehyde (MDA), tumor necrosis factor‐alpha (TNF‐α), cyclooxygenase‐2 (COX‐2), nuclear factor kappa‐B (NF‐κB), Beclin‐1, IL‐1β, bcl‐2 associated X protein (Bax), caspase‐3, light chain 3‐A (LC3‐A), and light chain 3‐B (LC3‐B) levels but reduced mammalian target of rapamycin (mTOR), b‐cell lymphoma‐2 (Bcl‐2), catalase (CAT), glutathione peroxidase (GPx), superoxide dismutase (SOD), glutathione (GSH) in lung tissues. The morin had effects on the level of these molecules in a way that is opposite to ACR. While ACR‐induced oxidative stress, apoptotic, autophagic, inflammatory responses, and may cause pulmonary dysfunction, the morin reduced ACR‐induced lung damage. Practical applications: ACR is a toxic chemical produced by frying, baking, roasting, or grilling foods with high starch content and has genotoxic, neurotoxic, and carcinogenic effects. As an antioxidant compound, the morin is obtained from plants or their products. It was aimed to detect possible protective effects of morin against ACR‐induced lung toxicity. It was detected that ACR‐induced oxidative stress, apoptotic, autophagic, inflammatory responses, and may cause pulmonary dysfunction, but the morin reduced ACR‐induced lung damage. Abstract : Acrylamide (ACR) has genotoxic, neurotoxic, and carcinogenic effects. Morin has an antioxidant feature, which is obtained from plants or their products. Morin reduces ACR‐induced oxidative stress, apoptotic, autophagic, inflammatory responses that induced lung damage.